Financial development and educational quality in Sub-Saharan Africa - Abubakar Musah; Godfred Aawaar (Cogent Economics & Finance, 2022)
This paper examines the effect of financial development on educational quality in Sub-Saharan Africa. This paper also analyses the interaction effect of public education financing and measures of financial development on quality of education in Sub-Saharan Africa. The study adopts the two-step system generalised method of moment (Two-Step System GMM) model in estimating the effect of financial development on educational quality and the interaction effect of financial development and public education financing on educational quality. We use data for the period 1990 to 2019 for 42 Sub-Saharan African countries obtained largely from the World Development Indicators of the World Bank and the International Monetary Fund (IMF) financial development index database. The results show that overall financial development, financial access, financial depth, and financial efficiency improve quality at the primary, secondary, and tertiary levels of education. We also find that public education financing improves quality at all levels of education. The results also show that public education financing positively moderates the nexus between measures of financial development and educational quality in Sub-Saharan Africa.
Keywords: 330; educational outcomes; educational quality; financial development; public education financing; Sub-Saharan Africa